30 years of economic transformation in CEE: Key five lessons for Belarus - Sierž Naūrodski; Aleś Alachnovič; Izabela Styczyńska; Krzysztof Głowacki; Jarosław Neneman; Pawel Swianiewicz; Andrzej Raczko; Kateryna Karunska (Center for Social and Economic Research (CASE), 2020)
Belarusian economy has been stagnating in 2011-2015 after 15 years of a high annual average growth rate. In 2015, after four years of stagnation, the Belarusian economy slid into a recession, its first since 1996, and experienced both cyclical and structural recessions. Since 2015, the Belarusian government and the National Bank of Belarus have been giving economic reforms a good chance thanks to gradual but consistent actions aimed at maintaining macroeconomic stability and economic liberalization. It seems that the economic authorities have sustained more transformation efforts during 2015-2018 than in the previous 24 years since 1991. As the relative welfare level in Belarus is currently 64% compared to the Central and Eastern Europe (CEE) countries average, Belarus needs to build stronger fundaments of sustainable growth by continuing and accelerating the implementation of institutional transformation, primarily by fostering elimination of existing administrative mechanisms of inefficient resource allocation. Based on the experience of the CEE countries' economic transformation, we highlight five lessons for the purpose of the economic reforms that Belarus still faces today: keeping macroeconomic stability, restructuring and improving the governance of state-owned enterprises, developing the financial market, increasing taxation efficiency, and deepening fiscal decentralization.
Keywords: P1; P2; P3; 330; economic transformation; post-communist transition; Belarus; Poland